Some aspects of foreign practice in counteracting premeditated murders by criminal police units (Bulletin of Kharkiv National University of Internal Affairs, 2021)
Some aspects of the international experience in counteracting premeditated murder by criminal police units have been studied. The main factors and features of formation and development of directions in counteraction to premeditated murders have been defined, the available models of counteraction to premeditated murders in activity of police divisions of separate countries have been allocated and analyzed.Based on the analysis of existing models and programmes to combat premeditated murder in some Western countries, our own model of counteraction to premeditated murder has been proposed, which needs to be implemented in Ukraine. The practice of development and implementation of measures of state, regional and city complex programmes of counteraction to criminal illegality in Ukraine deserves special attention. Premeditated homicide prevention programmes should be implemented with the broad involvement of various sections of the population, the public and volunteer movements on a European model. In order to activate Ukrainian youth to participate in various programmes aimed at crime prevention, it is necessary to use the experience of countries such as the Netherlands or Israel. Such positive experience should be the subject of separate study and implementation in Ukraine. Internal state policy should be formed on the development and implementation of such programmes. The main ways to promote the participation of citizens in the provision of voluntary free police assistance in combating criminal offenses can be: a) the creation of appropriate social advertising, which must be distributed on the Internet; b) popularization of the volunteer movement and voluntary groups of student youth in higher education institutions; c) organization of media projects to cover information on the number of volunteer units in Ukraine and individual cities, the results of their activities, achievements and future plans, speeches by the Minister of Internal Affairs, National Police Chief and other leaders on the specifics of police cooperation with citizens and benefits law enforcement agencies with the public and more.